NILAI-NILAI DALAM TRADISI MANAMPI PADI BASAMO DI DESA BAJUBANG LAUT SERTA RELEVANSINYA TERHADAP PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Rahmadani, Nuzul; Ryka Ayu Lestari; Cindy; Mega Afriani Sihite; Desi Kornia Sari; Audy Mita Amelina; Sentia Fita Ama; Dwi Nirmala Putri; Irma Sintiya Safitri; Tya Noviyanti; Nuraini Kumala Suri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Local wisdom constitutes an integral part of community life, preserving social and cultural values inherited across generations. Beyond serving as a life guide, these values have the potential to become a source of learning for character education. The Manampi Padi Basamo tradition in Bajubang Laut Village, Muara Bulian District, Batanghari Regency, Jambi Province, represents an example of local wisdom that is still preserved. This study aims to identify the values within this tradition and analyze their relevance to elementary school character education. Employing a qualitative descriptive approach, data were collected through observation, semi-structured interviews, and documentation. Data analysis followed the Miles and Huberman model, comprising reduction, display, and conclusion drawing. Findings revealed values such as mutual cooperation (gotong royong), togetherness, solidarity, responsibility, social care, family spirit, harmony, and spirituality. Among these, mutual cooperation (gotong royong), responsibility, and social care were found to be most relevant to character education. These values support the formation of cooperation, empathy, and social responsibility among students. The results indicate that local wisdom can be utilized as a contextual learning source for strengthening character education in elementary schools.